A Common Best Proximity Point Theorem for Ï•-dominated Pair (European Journal of Pure and Applied Mathematics, 2018)
In the present research, an interesting common best proximity point theorem for pairs of non-self-mappings is presented. It satises a weakly contraction-like condition, thereby producing common optimal approximate solutions of certain simultaneous xed point equations.